2017
DOI: 10.1186/s12974-017-0985-4
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic drug glyburide modulates depressive-like behavior comorbid with insulin resistance

Abstract: BackgroundAbundant reports indicated that depression was often comorbid with type 2 diabetes and even metabolic syndrome. Considering they might share common biological origins, it was tentatively attributed to the chronic cytokine-mediated inflammatory response which was induced by dysregulation of HPA axis and overactivation of innate immunity. However, the exact mechanisms remain obscure. Herein, we mainly focused on the function of the NLRP3 inflammasome to investigate this issue.MethodsMale C57BL/6 mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 77 publications
(82 reference statements)
1
22
0
Order By: Relevance
“…the improvement of metabolic parameters induced by prolonged administration of Met in mice fed an HFD were accompanied by a reduction of both anxiety and despair, whereas fluoxetine, the conventional antidepressant drug used herein as a positive control, failed to exert beneficial effects in the EPM. These results concur with previous preclinical studies pointing out that different classes of antidiabetic agents or adiponectin, a hormone exerting insulin-sensitizing action, produces antidepressant-like activities (Ho et al, 2012;Liu et al, 2012;Gupta et al, 2014;Su et al, 2017). In humans, a recent study also reported that Met favors depression recovery in patients with comorbid diabetes unveiling a strong correlation between improvement in plasma glycated hemoglobin levels and depression score (Guo and Lu, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…the improvement of metabolic parameters induced by prolonged administration of Met in mice fed an HFD were accompanied by a reduction of both anxiety and despair, whereas fluoxetine, the conventional antidepressant drug used herein as a positive control, failed to exert beneficial effects in the EPM. These results concur with previous preclinical studies pointing out that different classes of antidiabetic agents or adiponectin, a hormone exerting insulin-sensitizing action, produces antidepressant-like activities (Ho et al, 2012;Liu et al, 2012;Gupta et al, 2014;Su et al, 2017). In humans, a recent study also reported that Met favors depression recovery in patients with comorbid diabetes unveiling a strong correlation between improvement in plasma glycated hemoglobin levels and depression score (Guo and Lu, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…In marked contrast, insulin-sensitizing strategies exert neuroprotective/neurotrophic effects in rodents (Zhong et al, 2018). This has been reported with the antidiabetic agents liraglutide, glyburide, and metformin Su et al, 2017;Weina et al, 2018). Given the beneficial role of the serotonin (5-HT) system in the enhancement of brain plasticity (Quesseveur et al, 2013), the possibility that deficits in 5-HT neurotransmission underlie the comorbidity between T2D/IR and depression, has been raised.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that by inhibiting the activation of NLRP3 inflammasome, some hypoglycemic drugs exhibit antidepressant effects, whereas antidepressants exhibit the effect of regulating glucose metabolism. Glibenclamide is not only a sulfonylureas antidiabetic drug but also an effective inhibitor of NLRP3 inflammasome, which can regulate metabolic disorders caused by chronic stress and alleviate depressor-like behaviors by inhibiting the production of inflammasomes in the circulatory system [56,57]. Fluoxetine, a selective serotonin reuptake inhibitor, acts as an antidepressant and blood glucose regulator by inhibiting NLRP3 inflammasome to reduce inflammatory cytokines and regulate insulin signaling [58,59].…”
Section: Role Of Nlrp3 Inflammasome In Dmmentioning
confidence: 99%
“…The serum levels of IL-1β and homoeostatic model assessment-insulin resistance increase in patients with depression, and neuroinflammation and insulin resistance induced by metabolic imbalance can induce depressive disorder [78,79]. The activation of NLRP3 inflammasomes to produce IL-1β leads to the coexistence of depressive-like behavior and insulin resistance in CUMS mice [57].…”
Section: Role Of P2x7 Receptor and Nlrp3 Inflammasome In Ddmentioning
confidence: 99%
“…Some studies have found a strong association between depression and MetS [1][2][3][4][5][6][7][8]. While patients who suffer from depression have been found to have a two-fold increased risk of developing MetS [4,[9][10][11] one study [12] showed that those who suffered from twelve weeks of 'chronic stress' developed depressive symptoms, which over time became comorbid with insulin resistance. There is general agreement that insulin resistance is one of the principal contributing factors in the development of MetS.…”
Section: Introductionmentioning
confidence: 99%